Visualization of Equivalence in 2D Bivariate Fields. (10th July 2019) - Zheng, Boyan; Rieck, Bastian; Leitte, Heike; Sadlo, Filip
Abstract: In this paper, we show how the equivalence property leads to the novel concept of equivalent regions in mappings from ℝ n to ℝ n . We present a technique for obtaining these regions both in the domain and the codomain of such a mapping, and determine their correspondence. This enables effective investigation of variation equivalence within mappings, and between mappings in terms of comparative visualization. We implement our approach for n = 2, and demonstrate its utility using different examples.